Techno-Economic Analysis of Forest Residue Conversion to Sugar Using Three-Stage Milling as Pretreatment - Brandt, Kristin L.; Gao, Johnway; Wang, Jinwu; Wooley, Robert J.; Wolcott, Michael (Frontiers in Energy Research, 2018)
This study quantifies the cost of cellulosic sugar production using a fully-mechanical pretreatment process and fuel pellets as a co-product. The pretreatment reduces softwood forest harvest residuals to micron-sized amorphous particles. Energy consumption is minimized using a three-stage milling process. A techno-economic analysis was completed for a milling facility with saccharification and wood pellet manufacture. For the base case, concentrated sugar syrup can be produced for 0.496/kg of sugar. Sensitivity analyses were used to determine cost controlling variable, optimize the sugar cost and found that siting for this technology needs to strongly consider electricity cost and to a lesser extent local feedstock availability. If the sugar produced in this process is used to generate biofuel and is qualified for RIN credits through a life-cycle analysis, the effective cost could be reduced by 0.04-0.06/kg of sugar. An additional 0.067/kg savings is possible if the biofuel facility is located adjacent or on-site; the finished sugar syrup would not have to be concentrated for transportation. An optimized scenario, including the RIN credit, dilute sugar syrup, and favorable energy costs and consumption, could reduce the cost to 0.34/kg sugar compared to 0.496/kg for the base case.